Subcutaneous ureteral diversion and urethral stenting in the treatment of malignant urinary obstructions in cats: An integrative review of retrospective studies (Research, Society and Development, 2025)
Ureteral obstruction secondary to malignant disease in cats represents a significant clinical challenge due to the rapid progression of renal dysfunction and the aggressive local behavior of urogenital neoplasms. This study aimed to analyze, through an integrative review composed exclusively of retrospective investigations, the clinical outcomes associated with subcutaneous ureteral bypass (SUB) devices and ureteral stents in the management of malignant ureteral obstructions in felines. Methodological procedures included comprehensive extraction of data from seven retrospective studies, focusing on population characteristics, interventions, device patency, complication profiles and renal function outcomes. Findings demonstrated that SUB devices achieved superior long-term patency and functional stability compared to ureteral stents, particularly in cases involving infiltrative transitional cell carcinoma, although late complications such as recurrent urinary infection, partial obstruction and transmural gastrointestinal migration were identified. Ureteral stents, while effective for immediate decompression, exhibited higher rates of tumor-related reobstruction and lower tolerability in the lower urinary tract. Results emphasize that maintenance of device patency and infection control are critical determinants of survival and renal preservation. It is concluded that SUB devices offer superior long-term performance, though clinical decision-making should integrate individual tumor behavior and systemic condition. Future investigations should explore novel biomaterials, imaging-guided monitoring strategies and early predictors of device failure.